Inauthentic expressions of enthusiasm: Exploring the cost of emotional dissonance in teachers. (February 2018) - Taxer, Jamie L.; Frenzel, Anne C.
Abstract: Research on teacher enthusiasm has, to date, neglected how expressing enthusiasm influences teachers, particularly if they do not enjoy teaching at sufficiently high levels. To address this issue, we investigated whether teachers express teaching enthusiasm and experience teaching-related enjoyment at varying levels, and if so, how these varying levels relate to teachers' occupational well-being. In a preliminary study, we investigated whether teachers' ( N = 67) and students' ( N = 1489) ratings of teacher's expressed enthusiasm corresponded with one another and found that teachers can accurately assess their own level of expressed enthusiasm. Next, in two samples of teachers ( N 1 = 188 and N 2 = 263), using latent profile analyses we indeed found a latent group that was high in expressed teacher enthusiasm and comparably low in experienced teaching-related enjoyment. As expected, relative to the other groups in the samples, these groups had the most negative profiles with respect to their occupational well-being. Highlights: We examined the correlates of fake teacher enthusiasm. Teachers can accurately assess their own level of expressed enthusiasm. Expressed enthusiasm and experienced enjoyment are two separate constructs. A group of teachers who fake enthusiasm were found via a latent profile analysis. Faking enthusiasm was associated with the most negative profile.